The Impact Mechanisms of Digital Economy on China’s Manufacturing Industry’s Global Value Chain Division - Dongpo Li (Journal of World Economy, 2025)
With the changes in the world economic situation, the traditional manufacturing industry, which participates in the global value chain (GVC) by relying on low value-added production activities, no longer holds an advantage. China’s manufacturing industry is in urgent need of finding a new driving force for development and innovatively engaging in the GVC’s division of labor. At the same time, the scale and total volume of the domestic digital economy continue to increase, and the acceleration of industrial digitization and the smooth promotion of digital industrialization have significantly improved the overall quality of the social economy. This paper investigates how the digital economy influences China’s manufacturing industry’s role in the GVC, using literature review method to explore this relationship. The results reveal that there are three mechanisms of the digital economy’s impact on China’s manufacturing industry, which are direct impact, indirect impact and spatial spillover effect. Additionally, if the digital economy-related technologies are used to promote the reorganization of GVCs, it will enhance China’s manufacturing industry’s positioning within the GVCs’ division of labor, so that China’s manufacturing industry can get out of the “low-end lock-in” dilemma. Theoretically, this paper contributes to the understanding of how the digital economy affects the GVC in manufacturing. Practically, it offers insights into fostering the digital economy and advancing the manufacturing industry’s participation in the GVC.